Identifikasi Kebudayaan Lokal Kaili Sebagai Sumber Belajar Pada Tema Lingkungan Tempat Tinggalku di Kelas IV SDN 18 Banawa. - Mutmainnah, Ainun; Herlina, Herlina; Rizal, Rizal; Surahman, Surahman (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
The research problem in this study is: What aspects of the Kaili local culture are relevant as learning resources for the theme my living environment in grade IV of SDN 18 Banawa? The objective of this research is to describe the local culture and analyze its content as a learning resource for the theme my living Environment in grade IV of SDN 18 Banawa. This study employs a qualitative approach with a phenomenological design. The subjects of this research include teachers, grade IV students at SDN 18 Banawa, and community leaders in the Banawa subdistrict. Data collection techniques used are observation, interviews, literature review, and documentation. The data analysis techniques involve data reduction, data presentation, and drawing conclusions. Based on the results of the study conducted at SDN 18 Banawa, the local culture in the Banawa subdistrict that can be utilized as learning resources includes the Gonenggati folklore, Posisani songs, and Pusentasi tourism. This is evidenced by the Gonenggati folklore, Posisani songs, and Pusentasi tourism being local cultural elements still known by some members of the community, yet they have not been integrated into Grade IV learning, particularly in themes 1, 5, 7, 8, and 9. Utilizing Kaili local culture in the Banawa subdistrict as a learning resource is expected to help preserve local culture across generations.